Sustainable Islamic Education Based on Tawhid Values at MAN 2 Kota Probolinggo - Allifatur Rohma; Benny Prasetiya (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study aims to analyse the integration of Tawhid values in the implementation of sustainable Islamic education and its application in addressing the global challenges of Trends Shaping Education 2025 at MAN 2 Kota Probolinggo. The background of this study is based on the gap between the ideal concept of Islamic education grounded in Tawhid values and the learning practices in madrasahs, which still tend to be cognitively oriented and have not fully integrated the principles of sustainability and global challenges. This study employed a qualitative approach using a case study design. Data were collected through participant observation, in-depth interviews, and documentation, and were subsequently analysed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the integration of Tawhid values at MAN 2 Kota Probolinggo is carried out systematically and multidimensionally through policies, curriculum, learning processes, and school culture. This implementation is reflected in religious habituation, the application of the Love-Based Curriculum (KBC), and contextual learning that connects Tawhid values with contemporary issues such as technology and the environment. Furthermore, sustainable Islamic education in this madrasah demonstrates an adaptive character in responding to global challenges, particularly in the areas of digitalisation, social change, and environmental sustainability, without neglecting Islamic values as its foundation. Nevertheless, several obstacles remain in its implementation, including the heterogeneity of students’ backgrounds, the negative impact of digital technology, and the uneven internalisation of Tawhid values across institutional aspects. In conclusion, sustainable Islamic education based on Tawhid values at MAN 2 Kota Probolinggo represents a transformative educational model capable of integrating spiritual dimensions with global demands. This model has the potential to become an alternative framework for developing Islamic education that is adaptive, integrative, and oriented towards nurturing a generation that is faithful, morally grounded, and globally competitive.